Diversity of Long-tailed Macaque Food Trees (Macaca fascicularis) at The Tapos National Park Management Resort Area, Mount Gede Pangrango National Park - Dinda Rama Haribowo; Ardian Khairiah; Ence Maman; Dia Kurnia Alam; Hilal Fadlan Ramada; Indi Pitria Damayanti; Nida Khairun Nisaa; Salwa Fakhirah Alayafi; Rizky Reza Vahlevi; Feby Irfanullah; Lingga Heru Prasetio (Jurnal Biologi Tropis, 2023)
: Long-tailed macaque (LTM) are arboreal primates which have an ecological function as seed dispersers and as controllers of insect populations in their habitat. LTM populations were found in the Tapos National Park Management Resort forest area, MGPNP. The existence of food trees greatly influences the existence and activity of LTM, so knowledge about the diversity of LTM food trees in the Tapos National Park Management Resort area is very important to do. This research aims to determine the level of species dominance in the plant community and diversity of LTM food trees in the Pasir Koja and Pasir Beunyeng Forest Blocks, Tapos Management Resort Area.  Data collection on LTM food trees was carried out using the grid line method of vegetation analysis. Data processing was carried out by calculating the importance value index (IVI) of food tree vegetation and calculating the diversity index (H') of food tree species. The results showed that the highest IVI value in the Pasir Koja forest block was Bamboo (Bambusa sp.) with a value of 106.76%, while Ki acret (Spathodea campanulata) had the lowest IVI value of 10.65%. Meanwhile, the highest IVI value in the Pasir Beunyeng forest block was Kaliandra (Calliandra surinamensis) with an IVI of 166.60%, while reed bamboo (Gigantochloa atter) had the lowest IVI value of 17.62%. The food tree species diversity index in the Pasir Koja and Pasir Beunyeng forest blocks is categorized as low.